2023
DOI: 10.1111/ijal.12453
|View full text |Cite
|
Sign up to set email alerts
|

Teaching English to young learners in private sector of Iranian ELT: Challenges and local realities

Abstract: The growing phenomenon of (pre)primary English education worldwide has resulted in the rise in prominence of the discipline of teaching English to young learners (TEYL). Under the global forces and parents' pressure, early EFL learning has also turned into a pervasive trend in the marketized private sector of Iranian ELT as evidenced by the ever-growing number of classes of ever-younger learners. However, it is not clear what stands at its core because it has not received the attention it deserves, and reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 66 publications
2
3
0
Order By: Relevance
“…Most Asian countries introduce English into formal curricula from the primary stage, while at the preschool level, English provision is a bottom‐up initiative rather than mandated by policy (Zhou & Ng, 2016). The present study's findings echo research by Tavakol and Tavakoli (2023) on preschool English learning in Iran, which found that the government ban did not decrease micro‐level enthusiasm for early years English learning. However, this study differs from the Iranian context where English is banned for concerns about Westernisation and cultural invasion (Tavakol & Tavakoli, 2023).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Most Asian countries introduce English into formal curricula from the primary stage, while at the preschool level, English provision is a bottom‐up initiative rather than mandated by policy (Zhou & Ng, 2016). The present study's findings echo research by Tavakol and Tavakoli (2023) on preschool English learning in Iran, which found that the government ban did not decrease micro‐level enthusiasm for early years English learning. However, this study differs from the Iranian context where English is banned for concerns about Westernisation and cultural invasion (Tavakol & Tavakoli, 2023).…”
Section: Discussionsupporting
confidence: 76%
“…The present study's findings echo research by Tavakol and Tavakoli (2023) on preschool English learning in Iran, which found that the government ban did not decrease micro‐level enthusiasm for early years English learning. However, this study differs from the Iranian context where English is banned for concerns about Westernisation and cultural invasion (Tavakol & Tavakoli, 2023). None of the education officials and school participants in the Hefei study expressed such concerns.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations